2017
DOI: 10.1117/1.jrs.11.016042
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake damage mapping by using remotely sensed data: the Haiti case study

Abstract: Abstract. This work proposes methodologies aimed at evaluating the sensitivity of optical and synthetic aperture radar (SAR) change features obtained from satellite images with respect to the damage grade due to an earthquake. The test case is the Mw 7.0 earthquake that hit Haiti on January 12, 2010, located 25 km west-south-west of the city of Port-au-Prince. The disastrous shock caused the collapse of a huge number of buildings and widespread damage. The objective is to investigate possible parameters that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…It is worth noticing that the damage classification (low, medium and high) is based on a relative scale. Romaniello et al (2016) have shown the correlation between this kind of damage classification and the collapse ratio, defined as the ratio between the number of collapsed buildings and the total number of buildings within a polygon. Therefore, high damage can indicate many collapses within a city block.…”
Section: Figure 2: Fst Methods Block Schemementioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noticing that the damage classification (low, medium and high) is based on a relative scale. Romaniello et al (2016) have shown the correlation between this kind of damage classification and the collapse ratio, defined as the ratio between the number of collapsed buildings and the total number of buildings within a polygon. Therefore, high damage can indicate many collapses within a city block.…”
Section: Figure 2: Fst Methods Block Schemementioning
confidence: 99%
“…Previous studies, carried out during the European APhoRISM project, allowed us to identify the features having a good sensitivity to damage at object scale (Romaniello et al (2016)). Following the project outcomes, in the present work we used the NDI, and two quantities coming from the Information Theory, the KLD and the MI.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, the devastating earthquake disaster has caused great loss to human life and property (Geiss and Taubenboeck, 2013;Romaniello et al 2017). It is very important to carry out post-earthquake disaster assessment to obtain the postearthquake disaster information timely and effectively (Romaniello et al 2017;Tong et al 2012). Building damage is often considered as the most important sign of post-earthquake disaster.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed information can be obtained via interferometric SAR (InSAR) data, which are based on the differences in the phase information of the returning signals of two temporal images [10]. To detect and assess the damage caused by natural disasters, most published studies use either InSAR coherence [11][12][13][14][15] or the SAR intensity correlation [3,16,17], or both [18][19][20]. The accurate mapping that is essential to the planning and execution of an emergency response to a natural disaster can be obtained by using very high resolution (VHR) SAR data, such as that generated by the TerraSAR-X satellite.…”
Section: Introductionmentioning
confidence: 99%